2022
DOI: 10.3390/molecules27196736
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Effects of Resveratrol on Wound Healing: A Comprehensive Review

Abstract: Resveratrol (RSV) is a natural extract that has been extensively studied for its significant anti-inflammatory and antioxidant effects, which are closely associated with a variety of injurious diseases and even cosmetic medicine. In this review, we have researched and summarized the role of resveratrol and its different forms of action in wound healing, exploring its role and mechanisms in promoting wound healing through different modes of action such as hydrogels, fibrous scaffolds and parallel ratio medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…In mouse models of cutaneous cancers, resveratrol inhibited tumor growth, lowered tumor volume and weight, suppressed metastasis tendency, and increased survival time [257,258,261,265,270,271]. Also, resveratrol displayed beneficial effects in wound healing [272].…”
Section: Bitter Phytochemicals Active On Skin Inflammation Skin Carci...mentioning
confidence: 99%
“…In mouse models of cutaneous cancers, resveratrol inhibited tumor growth, lowered tumor volume and weight, suppressed metastasis tendency, and increased survival time [257,258,261,265,270,271]. Also, resveratrol displayed beneficial effects in wound healing [272].…”
Section: Bitter Phytochemicals Active On Skin Inflammation Skin Carci...mentioning
confidence: 99%
“…In several experimental murine models, RSV treatment increased cutaneous wound healing, inhibited excessive scarring, prevented skin photoaging, and stimulated chronic wound healing [215][216][217][218]. In STZ-induced C57/B6 diabetic mice, RSV 10 µmol/L, injected around the injury, induced M2 macrophage polarization, decreased the level of pro-inflammatory cytokines (TNF-α, IL-6, IL-1β), and accelerated the skin wound healing [219].…”
Section: Wound Healing Propertiesmentioning
confidence: 99%
“…As with many other natural compounds, RSV exerts a biphasic effect. Indeed, several studies have demonstrated that high doses of RSV lead to a decline in cell viability, while low doses could determine a proliferative effect [ 48 , 49 ]. Rocha et al investigated the effect of RSV from 25 to 500 µM, for 24 h, against immortalized fibroblasts (HaCaT cell lines).…”
Section: In Vitro and In Vivo Chemopreventive And Anticancer Activiti...mentioning
confidence: 99%